Calvarial Regeneration With Use of Acellular Dermal Matrix in Aplasia Cutis Congenita. Issue 6 (September 2015) - Mericli, Alexander F.; Chen, Kevin; Murariu, Daniel; Jane, John A.; Lin, Kant Y.
Abstract : Abstract: Aplasia cutis congenital (ACC) is a rare congenital anomaly, most commonly affecting the scalp, with a variable penetrance ranging from a small (<2 cm 2 ) area of missing skin to large defects characterized by absent skin, subcutaneous tissue, calvarium, and dura. Calvarial reconstruction in ACC can be challenging. Due to exposed neurologic structures, in large defects, ACC has a high mortality rate. A stable reconstruction is optimally achieved shortly after birth to minimize complications. Herein the authors present a case of a neonate with an extensive (4.5 × 7 cm) cutis aplasia defect associated with absent skin, subcutaneous tissue, calvarium, dura, and with exposed cortical surface and sagittal sinus. This defect was successfully reconstructed in a single stage with the use of an acellular dermal matrix/skin graft construct. The acelluar dermal matrix served as a scaffold for tissue ingrowth, promoting regeneration of the bony calvarium as well as soft tissue. At 18-month follow-up, the patient exhibits a 50% smaller calvarial defect as well as stable skin coverage.